Black carp IRF5 interacts with TBK1 to trigger cell death following viral infection. (November 2019) - Yang, Can; Liu, Liqun; Liu, Ji; Ye, Zi; Wu, Hui; Feng, Pinghui; Feng, Hao
Abstract: Interferon regulated factor 5 (IRF5) is a key regulator of inflammatory responses in human and mammals; however, its role in teleost remains largely unknown. In this study, IRF5 homologue of black carp ( Mylopharyngodon piceus ) has been cloned and characterized, which possesses conservation in structure and sequence to its mammalian counterparts. Black carp IRF5 (bcIRF5) was characterized as a predominantly cytosolic protein by immunofluorescent staining and showed little IFN promoter-inducing ability in reporter assay. The direct association between bcIRF5 and black carp TBK1 (bcTBK1) were identified through co-immunoprecipitation assay, and co-expressed bcIRF5 in EPC cells suppressed bcTBK1-mediated IFN promoter transcription in reporter assay. Surprisingly, the titer of grass carp reovirus (GCRV) in the media of EPC cells co-expressing bcIRF5 and bcTBK1 was obviously lower than that of EPC cells expressing bcTBK1 alone. It was interesting that expression of bcIRF5 and/or bcTBK1 in EPC cells showed little effect on cell growth; however, the survival ratio of EPC cells co-expressing bcTBK1 and bcIRF5 post GCRV infection was much lower than that of EPC cells expressing bcIRF5 or bcTBK1 alone. These results indicate that bcIRF5 negatively regulates bcTBK1-mediated IFN signaling in healthy cells; however, it correlates with bcTBK1 and triggers cell death to inhibit the virus replication during the innate immune activation. Highlights: bcIRF5 interacts with bcTBK1. bcIRF5 inhibits bcTBK1-mediated IFN signaling in healthy cells. bcIRF5 correlates with bcTBK1 to trigger cell death to inhibit the virus replication after virus infection.